2009
DOI: 10.1001/archinternmed.2009.214
|View full text |Cite
|
Sign up to set email alerts
|

Thiazolidinediones and Fractures in Men and Women

Abstract: Both men and women who take thiazolidinediones could be at increased risk of fractures. Pioglitazone may be more strongly associated with fractures than rosiglitazone. Larger observational studies are needed, and fracture data from clinical trials need to be fully published so that fracture risks can be known with greater certainty.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
75
2
4

Year Published

2010
2010
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 126 publications
(89 citation statements)
references
References 31 publications
5
75
2
4
Order By: Relevance
“…Our data indeed show that in contrast to MET, serum sclerostin levels increased in patients treated with PIO and that this was associated with a significant increase in serum CTX levels, despite adequate glycemic control. Over the past decade, evidence has been accumulating on the detrimental effect of TZDs on the skeleton, decreasing bone mass and increasing fracture risk in both men (33,34,35) and women with diabetes mellitus (4,33,35,36,37,38,39). This deleterious effect of TZDs on the skeleton is generally attributed to the activation of PPARg in the bone marrow by these agents, leading to preferential stimulation of adipogenesis at the cost of osteoblastogenesis (5).…”
Section: Discussionmentioning
confidence: 99%
“…Our data indeed show that in contrast to MET, serum sclerostin levels increased in patients treated with PIO and that this was associated with a significant increase in serum CTX levels, despite adequate glycemic control. Over the past decade, evidence has been accumulating on the detrimental effect of TZDs on the skeleton, decreasing bone mass and increasing fracture risk in both men (33,34,35) and women with diabetes mellitus (4,33,35,36,37,38,39). This deleterious effect of TZDs on the skeleton is generally attributed to the activation of PPARg in the bone marrow by these agents, leading to preferential stimulation of adipogenesis at the cost of osteoblastogenesis (5).…”
Section: Discussionmentioning
confidence: 99%
“…More recently, Habib et al [70] showed an increased risk in women >65 years, but not in men and Dormuth et al [71], showed a higher risk with pioglitazone, affecting men and women.…”
Section: Bone Fracturesmentioning
confidence: 98%
“…The pleiotropic effects of TZDs include decreasing insulin resistance, hyperplasia of pancreatic beta cells (potential to improve beta cell function), improve the lipid parameters, alteration in adipokines (increase the adiponectin, decrease resistin), decreasing C-reactive protein levels, improving endothelial function, reducing restenosis rates in subjects with coronary artery disease, mild improvement in blood pressure and decreasing urinary albumin excretion. However, epidemiological and observational studies indicate that TZD therapy with rosiglitazone and Pioglitazone is also associated with an increased risk of fractures [10][11][12][13][14][15]. TZDs improve glycemic control through activation of the peroxisome proliferator-activated receptor (PPAR)-Îł. TZDs inhibit osteoblastogenesis [16][17][18] and suppress markers of osteoblast activity [16], and cause increased osteoclastogenesis [19], which results in decreased bone mass.…”
Section: Introductionmentioning
confidence: 99%